2012
DOI: 10.1088/2041-8205/759/2/l34
|View full text |Cite
|
Sign up to set email alerts
|

Wd0837+185: The Formation and Evolution of an Extreme Mass-Ratio White-Dwarf-Brown-Dwarf Binary in Praesepe

Abstract: There is a striking and unexplained dearth of brown dwarf companions in close orbits (< 3AU) around stars more massive than the Sun, in stark contrast to the frequency of stellar and planetary companions. Although rare and relatively short-lived, these systems leave detectable evolutionary end points in the form of white dwarf -brown dwarf binaries and these remnants can offer unique insights into the births and deaths of their parent systems. We present the discovery of a close (orbital separation ∼ 0.006 AU)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 40 publications
3
33
0
Order By: Relevance
“…Despite many candidate systems being discovered from all-sky surveys (e.g. Girven et al 2011;Debes et al 2011), only eight postcommon envelope systems have been confirmed: GD1400 (WD+L6, P=9.98 hrs; Farihi & Christopher 2004;Dobbie et al 2005;Burleigh et al 2011), WD0137-349 (WD+L6-E-mail: slc25@le.ac.uk † Hubble Fellow L8, P=116 min; Maxted et al 2006;Burleigh et al 2006a), WD0837+185 (WD+T8, P=4.2 hrs; Casewell et al 2012), NLTT5306 (WD+L4-L7, P=101.88 min; Steele et al 2013), SDSS J155720.77+091624.6 (WD+L3-L5, P=2.27 hrs); Farihi et al 2017, SDSS J1205-0242 (WD+L0, P=71.2 min; Parsons et al 2017;Rappaport et al 2017), SDSS J1231+0041 (WD+M/L, P=72.5 min; Parsons et al 2017) and SDSS J141126.20+200911.1, (WD+T5, P=121.73 min; Beuermann et al 2013;Littlefair et al 2014). All of these systems have survived a phase of common-envelope evolution, resulting in the close binary system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite many candidate systems being discovered from all-sky surveys (e.g. Girven et al 2011;Debes et al 2011), only eight postcommon envelope systems have been confirmed: GD1400 (WD+L6, P=9.98 hrs; Farihi & Christopher 2004;Dobbie et al 2005;Burleigh et al 2011), WD0137-349 (WD+L6-E-mail: slc25@le.ac.uk † Hubble Fellow L8, P=116 min; Maxted et al 2006;Burleigh et al 2006a), WD0837+185 (WD+T8, P=4.2 hrs; Casewell et al 2012), NLTT5306 (WD+L4-L7, P=101.88 min; Steele et al 2013), SDSS J155720.77+091624.6 (WD+L3-L5, P=2.27 hrs); Farihi et al 2017, SDSS J1205-0242 (WD+L0, P=71.2 min; Parsons et al 2017;Rappaport et al 2017), SDSS J1231+0041 (WD+M/L, P=72.5 min; Parsons et al 2017) and SDSS J141126.20+200911.1, (WD+T5, P=121.73 min; Beuermann et al 2013;Littlefair et al 2014). All of these systems have survived a phase of common-envelope evolution, resulting in the close binary system.…”
Section: Introductionmentioning
confidence: 99%
“…Along with CVs containing a brown dwarf, these few systems represent the lowest mass objects that can survive common envelope evolution, as well as informing us about the mass loss processes as the giant evolves (e.g. Rappaport et al (2017); Casewell et al (2012)). In the case of SDSS J155720.77+091624.6, there is not only a brown dwarf that has survived the common envelope evolution, but also a dust disk that may represent the remnants of a planetary system (Farihi et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding LB 5959, we have already mentioned in Sect. 2 that Casewell et al (2012) observations suggest the presence of a companion with mass equal to 25-30 M Jup , although Gaia DR2 parameters are consistent with this object being a single star. In the scenario envisaged by Casewell et al (2012) the substellar companion must have been engulfed by the WD progenitor during the AGB evolu-tion.…”
Section: Summary and Discussionmentioning
confidence: 79%
“…2 that Casewell et al (2012) observations suggest the presence of a companion with mass equal to 25-30 M Jup , although Gaia DR2 parameters are consistent with this object being a single star. In the scenario envisaged by Casewell et al (2012) the substellar companion must have been engulfed by the WD progenitor during the AGB evolu-tion. This common envelope interaction may therefore have modified the IFMR of this object, compared to our estimates based on single-star evolution for the progenitor.…”
Section: Summary and Discussionmentioning
confidence: 79%
“…There are a handful of confirmed white dwarfbrown dwarf binaries in compact orbits which suggest that, despite engulfment, the brown-dwarf survives post-main sequence evolution relatively unscathed (Farihi & Christopher 2004;Maxted et al 2006;Casewell et al 2012;Steele et al 2013). The compact orbits lead to tidally synchronous orbits and significant differences between dayside and nightside brown-dwarf surface temperatures (Casewell et al 2015).…”
Section: Region Iii: High Tempertaure Small Radiusmentioning
confidence: 99%